Um olhar Sociofuncionalista no estudo da estratificação/variação das orações completivas e parentéticas (A Sociofunctionalist look at the study of stratification/variation of completive and parenthetical clauses) - Amorim, Vânia Raquel Santos (2021)
In this work, we aim to investigate the variation of the subjunctive in parenthetical clauses initiated by que and in completive clauses introduced by the complementizer que, anchored in the Sociofunctionalist approach. The sample was extracted from 24 informants of the Corpus Popular de Vitória da Conquista (Corpus PPVC). In the quantitative study, regarding the linguistic factors, the group of factors ‘clause type’ indicated higher subjunctive indices in completive clauses. Besides, the subjunctive was favored through the semantic value of the verb of the matrix clause and by the structure of the clause's assertiveness. Concerning extralinguistic factors, the data reveal that the standard variant is concentrated in the female gender and in those informants who had a systematized/formal education. In general terms, the result of this research, from the sociolinguistic point of view, indicates a stable variation and, from the functionalist point of view, a process of Grammaticalization.